Political conflict, green capabilities, and growth patterns in a Kaleckian small open economy - José Eduardo Alatorre; Julia Juarez; Juan Carlos Moreno-Brid; Gabriel Porcile (Levy Economics Institute of Bard College, 2024)
The paper presents a Kaleckian extended model exploring sustainable development, defined as growth that is economically stable, socially inclusive, and environmentally respectful. The model links CO2 emission trends with public investments in green capabilities, represented by the share of renewables in total energy supply. It incorporates three key actors: green capitalists (G), brown capitalists (B), and workers (R), whose alliances influence taxes, social expenditure, and green capabilities investments. Three political coalitions are formed: green-red (GR), green-brown (GB), and red-brown (RB). The GR coalition promotes sustainable and inclusive growth but may face trade imbalances depending on public investment's ability to boost non-price competitiveness. The GB alliance yields sustainable but non-inclusive growth with a high long-term deficit. The RB coalition results in environmentally unsustainable outcomes but may produce stable growth with income redistribution during high commodity export demand. Applying the model to Mexico highlights fiscal space challenges for public investment and income redistribution amidst emissions reduction targets.
Keywords: B50; Q43; Q56; 330